2010
DOI: 10.1007/s10818-010-9091-8
|View full text |Cite
|
Sign up to set email alerts
|

A bottom-up re-estimation of global fisheries subsidies

Abstract: Overcapacity, Overfishing, World Trade Organization, Fuel subsidies, F01, H25, L79, Q22, Q28,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
216
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(223 citation statements)
references
References 13 publications
4
216
0
3
Order By: Relevance
“…Rapid emissions reduction may, therefore, require policy intervention. A frequently cited candidate is the removal of distortionary fuel subsidies and tax concessions (Sumaila et al, 2010), which reduce the effective cost of oil to vessel operators to support the fishing industry. Such policies are not found in Iceland but are prevalent throughout the rest of the Nordic region (Martini, 2012) and can lead to substitution of oil for other inputs, as well as weaker incentives to invest in improved fuel efficiency.…”
Section: Improving Fuel Efficiencymentioning
confidence: 99%
“…Rapid emissions reduction may, therefore, require policy intervention. A frequently cited candidate is the removal of distortionary fuel subsidies and tax concessions (Sumaila et al, 2010), which reduce the effective cost of oil to vessel operators to support the fishing industry. Such policies are not found in Iceland but are prevalent throughout the rest of the Nordic region (Martini, 2012) and can lead to substitution of oil for other inputs, as well as weaker incentives to invest in improved fuel efficiency.…”
Section: Improving Fuel Efficiencymentioning
confidence: 99%
“…The FAO Technical Guidelines for Responsible Fisheries [11] is also an attempt to associate fisheries policies and the management of small-scale fisheries, supporting food security and addressing poverty. Sumaila et al [12] addressed beneficial subsidies associated with investment in the natural capital of fisheries by reporting community development programs in rural fisheries, involving local communities/ livelihoods integrated into policy demands. Defeo et al [13] addressed the importance of the social-ecological systems of small-scale fisheries considering the effects of climate change, markets and governance: for example, they concluded that weak governance, market globalization, fishing pressure and climate change contributed to resource depletion in shellfisheries of Latin America.…”
Section: The Journal Of the Marine Science Research And Developmentmentioning
confidence: 99%
“…To be fair this is true of both proponents of ITQ fisheries and community-managed fisheries, both of which favour current resource users over the general public. This is a dubious position to take in many real world fisheries where the existing users have typically been the recipients of decades of massive subsidies and state granted monopolies [18]. It also takes for granted the existence of some redistribution systems (income taxes are usually put forward as solving the problem), while ignoring the fact that most fisheries benefit from special tax treatment and tax exemptions (subsidies) that prevent this redistribution.…”
Section: Regulation Versus Persuasionmentioning
confidence: 99%